In Search of Neural Correlates of Social Comparisons: An Integrative Research Design - Oded Stark (Institute of Labor Economics (IZA), 2025)
We review the research questions that guided studies seeking to detect brain activity arising from engagement in upward social comparisons, in particular comparisons of a relative variable of interest and a variable-based rank. To streamline, and without loss of generality, we refer throughout this paper to income as the comparison variable. For close scrutiny, we choose two representative and influential studies, Fliessbach et al. (2007) and Zink et al. (2008). Each of these studies is representative of a family of studies conducted in the same vein, and each examined in isolation neural correlates, either of income-based relative deprivation, in short relative deprivation, or of income-based rank. We argue that a deeper research question than those to which the Fliessbach et al. and Zink et al. studies attended pertains to the interaction and tradeoffs between relative deprivation and income-based rank and, consequently, to the corresponding activity in areas of the brain. We propose a method for formulating an improved, integrative research design, and we remark on the expected corresponding gain.
Keywords: A12; A13; D01; D91; 330; social comparisons; brain activity; neural representation of social comparisons; neural correlates; integrative research design